L’approdo del metodo normale nella formazione del maestro italiano - Matteo Morandi (Studi sulla Formazione)
This essay retraces the last stage in the articulated history of the normal method, after the Pietist, the Habsburg Chamberlain and the French revolutionary seasons. In Restoration Italy, “normal” is no more than a synonym for method (for good method), without further specification, so much so that “normal” or “method” schools are called the schools for the teachers training, on which Piedmont, for example, would focus from 1840 onwards. This is the starting point for the so-called Piedmontese Methodical Movement, inspired by the lesson of Ferrante Aporti and made up of politicians and schoolmen such as Giovanni Antonio Rayneri, Domenico Berti, Vincenzo Troya, Carlo Boncompagni, Vincenzo Gerelli and Agostino Fecia, whose ideas would inspire teacher training in united Italy.